Creating and dominating new markets - Meyer, Peter, 1954- (AMACOM, 2002)
Publisher Fact Sheet Offers managers, executives, and business strategies to emulate the success of savvy market creators such as Microsoft, FedEx, and AOL.
Keywords: New products.; Marketing.; Creative ability in business.; Marketing; Créativité dans les affaires.; marketing.; BUSINESS & ECONOMICS -- Marketing -- General.; BUSINESS & ECONOMICS -- Distribution.; Creative ability in business; New products